Mass Media Use to Learn About COVID-19 and the Non-intention to Be Vaccinated Against COVID-19 in Latin America and Caribbean Countries - Bendezu-Quispe, Guido; Benites-Meza, Jerry K.; Urrunaga-Pastor, Diego; Herrera-Añazco, Percy; Uyen-Cateriano, Angela; Rodriguez-Morales, Alfonso J.; Toro-Huamanchumo, Carlos J.; Hernandez, Adrian V.; Benites-Zapata, Vicente A. (Frontiers in Medicine, 2022)
Background: The Latin American and Caribbean (LAC) region has been one of the regions most affected by the COVID-19 pandemic, with countries presenting some of the highest numbers of cases and deaths from this disease in the world. Despite this, vaccination intention is not homogeneous in the region, and no study has evaluated the influence of the mass media on vaccination intention. The objective of this study was to evaluate the association between the use of mass media to learn about COVID-19 and the non-intention of vaccination against COVID-19 in LAC countries. Methods: An analysis of secondary data from a Massachusetts Institute of Technology (MIT) survey was conducted in collaboration with Facebook on people's beliefs, behaviors, and norms regarding COVID-19. Crude and adjusted prevalence ratios (aPR) with their respective 95% confidence intervals (95%CI) were calculated to evaluate the association between the use of mass media and non-vaccination intention using generalized linear models of the Poisson family with logarithmic link. Results: A total of 350,322 Facebook users over the age of 18 from LAC countries were included. 50.0% were men, 28.4% were between 18 and 30 years old, 41.4% had a high school education level, 86.1% lived in the city and 34.4% reported good health condition. The prevalence of using the mass media to learn about COVID-19 was mostly through mixed media (65.8%). The non-intention of vaccination was 10.8%. A higher prevalence of not intending to be vaccinated against COVID-19 was found in those who used traditional media (aPR=1.36; 95%CI: 1.29-1.44; p<0.001) and digital media (aPR=1.70; 95%CI: 1.24-2.33; p=0.003) compared to those using mixed media. Conclusion: We found an association between the type of mass media used to learn about COVID-19 and the non-intention of vaccination. The use of only traditional or digital information sources were associated with a higher probability of non-intention to vaccinate compared to the use of both sources.